Nationwide trends in residential and non-residential out-of-hospital cardiac arrest and differences in bystander cardiopulmonary resuscitation. (June 2020) - Ting, Priscilla Zi Yin; Ho, Andrew Fu Wah; Lin, Xinyi; Shahidah, Nur; Blewer, Audrey; Ng, Yih Yng; Leong, Benjamin Sieu-Hon; Gan, Han Nee; Mao, Desmond Renhao; Chia, Michael Yih Chong; Cheah, Si Oon; Ong, Marcus Eng Hock
Abstract: Aims: Singapore is highly-urbanized, with >90% of the population living in high-rise apartments. She has implemented several city-wide interventions such as dispatcher-assisted CPR, community CPR training and smartphone activation of volunteers to increase bystander CPR (BCPR) rates for out-of-hospital cardiac arrest (OHCA). These may have different impact on residential and non-residential OHCA. We aimed to evaluate the characteristics, processes-of-care and outcome differences between residential and non-residential OHCA and study the differences in temporal trends of BCPR rates. Methods: This was a national, observational study in Singapore from 2010 to 2016, using data from the prospective Pan-Asian Resuscitation Outcomes Study. The primary outcome was survival (to-discharge or to-30-days). Multivariate logistic regression was performed to determine the effect of location-type on survival and a test of statistical interaction was performed to assess the difference in the temporal relationship of BCPR rates between location-type. Results: 8397 cases qualified for analysis, of which 5990 (71.3%) were residential. BCPR and bystander automated external defibrillator (AED) rates were significantly lower in residential as compared to non-residential arrests (41.0% vs 53.6%, p < 0.01; 0.4% vs 10.8%, p < 0.01 respectively). Residential BCPR increased from 15.8% (2010) to 57.1% (2016). Residential cardiac arrests had lower survival-to-discharge (2.9% vs 10.1%, p < 0.01). Multivariate logistic regression analysis showed that location-type had an independent effect on survival, with residential arrests having poorer survival compared to non-residential cardiac arrests (adjusted OR 0.547 [0.435–0.688]). A test of statistical interaction showed a significant interaction effect between year and location-type for bystander CPR, with a narrowing of differences in bystander CPR between residential and non-residential cardiac arrests over the years. Conclusion: Residential cardiac arrests had poorer bystander intervention and survival from 2010 to 2016 in Singapore. BCPR had improved more in residential arrests compared to non-residential arrests over a period of city-wide interventions to improve BCPR.